Checkpoint CD24 function on tumor and immunotherapy - Huang, Shiming; Zhang, Xiaobo; Wei, Yingtian; Xiao, Yueyong (Frontiers in Immunology, 2024)
CD24 is a protein found on the surface of cells that plays a crucial role in the proliferation, invasion, and spread of cancer cells. It adheres to cell membranes through glycosylphosphatidylinositol (GPI) and is associated with the prognosis and survival rate of cancer patients. CD24 interacts with the inhibitory receptor Siglec-10 that is present on immune cells like natural killer cells and macrophages, leading to the inhibition of natural killer cell cytotoxicity and macrophage-mediated phagocytosis. This interaction helps tumor cells escape immune detection and attack. Although the use of CD24 as a immune checkpoint receptor target for cancer immunotherapy is still in its early stages, clinical trials have shown promising results. Monoclonal antibodies targeting CD24 have been found to be well-tolerated and safe. Other preclinical studies are exploring the use of chimeric antigen receptor (CAR) T cells, antibody-drug conjugates, and gene therapy to target CD24 and enhance the immune response against tumors. In summary, this review focuses on the role of CD24 in the immune system and provides evidence for CD24 as a promising immune checkpoint for cancer immunotherapy.